Annabel L. Kim. Cacaphonies: The Excremental Canon of French Literature. UP of Minnesota, 2022. - gloria kwok (Studies in 20th & 21st Century Literature, 2023)
Review of Annabel L. Kim. Cacaphonies: The Excremental Canon of French Literature. UP of Minnesota, 2022. 288 pp.
Keywords: contemporary French literature; literary waste studies